2018
DOI: 10.1016/j.sjbs.2017.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of potassium bromate administration on renal and hepatic tissues of Swiss mice

Abstract: Potassium bromate (KBrO) is widely used as a food additive and is a major water disinfection by-product. The present study reports the side effects of KBrO administration in Swiss mice. Animals were randomly divided into three groups: control, low dose KBrO (100 mg/kg/day) and high dose KBrO (200 mg/kg/day) groups. Administration of KBrO led to decreased white blood corpuscles (WBCs), red blood corpuscles (RBCs) and platelets count in the animals of both the high and the low dose groups. Altered lipid profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Owing to its hazardous potential, the use of KBrO 3 has been banned in several countries (Oloyede and Sunmonu, 2009). The adverse side effects of KBrO 3 include hematological alterations and altered histomorphology and normal functioning of liver and kidney (Altoom et al, 2018). Several studies have demonstrated reduced body weight gain, suppressed locomotor activities, and ataxia in adult mice following bromate ingestion (Ajarem et al, 2016; Altoom et al, 2018; Kurokawa et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its hazardous potential, the use of KBrO 3 has been banned in several countries (Oloyede and Sunmonu, 2009). The adverse side effects of KBrO 3 include hematological alterations and altered histomorphology and normal functioning of liver and kidney (Altoom et al, 2018). Several studies have demonstrated reduced body weight gain, suppressed locomotor activities, and ataxia in adult mice following bromate ingestion (Ajarem et al, 2016; Altoom et al, 2018; Kurokawa et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Appearance of the vaginal plug was considered the first day of gestation. Pregnant mice were randomly divided into two groups each comprising 10 mothers as follows: Control group (Control): Pregnant mice received 1 ml drinking water daily by oral intubation from gestational day (D) 5 to postnatal D21. Bromate-exposed group (KBrO 3 ): Pregnant mice received a daily oral dose of KBrO 3 (200 mg/kg body weight; Altoom et al, 2018; Kurokawa et al, 1990) dissolved in bottled drinking water by oral intubation from gestational D5 to postnatal D21. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium bromate (KBrO 3 ) has been known as a mutagen agent inducing carcinogenesis, and humans might be exposed to potassium bromate either through drinking water (as a byproduct of ozonisation) or bakery products (as a food additive) . It has been shown that potassium bromate induces oxidative stress and DNA damage in cell culture and inhibits apoptotic pathways in experimental animal studies . In this study, we aimed to investigate possible cancer‐induced effect of potassium bromate in normal colon cell line by determining the molecules in apoptosis pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Its traces can be cited in multiple packaged and municipality supply water after ozonization during the filtration process [ 1 ]. Also, it is used in improving flour quality and dough conditioning in the baking industry as well as in the preparation of beverages, cheese, and fish paste [ 2 4 ]. Hence, PB in various consumer items poses mild to severe toxicity to critical organs, viz., the kidney, liver, and brain in the living systems [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%